Lipid metabolism in Calanus finmarchicus is sensitive to variations in predation risk and food availability - Elise Skottene (Nature Portfolio, 2020)
Abstract Late developmental stages of the marine copepods in the genus Calanus can spend extended periods in a dormant stage (diapause) that is preceded by the accumulation of large lipid stores. We assessed how lipid metabolism during development from the C4 stage to adult is altered in response to predation risk and varying food availability, to ultimately understand more of the metabolic processes during development in Calanus copepods. We used RNA sequencing to assess if perceived predation risk in combination with varied food availability affects expression of genes associated with lipid metabolism and diapause preparation in C. finmarchicus. The lipid metabolism response to predation risk differed depending on food availability, time and life stage. Predation risk caused upregulation of lipid catabolism with high food, and downregulation with low food. Under low food conditions, predation risk disrupted lipid accumulation. The copepods showed no clear signs of diapause preparation, supporting earlier observations of the importance of multiple environmental cues in inducing diapause in C. finmarchicus. This study demonstrates that lipid metabolism is a sensitive endpoint for the interacting environmental effects of predation pressure and food availability. As diapause may be controlled by lipid accumulation, our findings may contribute towards understanding processes that can ultimately influence diapause timing.